Successful Retrieval of Fish Hook From Indian Flap-Shelled Turtle (Lissemys punctata) via Intra-oral Approach - Gautam, Deepesh; Singh, Deepa; Kumar, Adesh; Patra, Sarit Kumar; Ahirwar, Manoj Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Lissemys punctata, an Indian flap-shelled turtle is a fresh water species found widespread and common in South Asia. Injuries due to entangled fish hook is the most common affection reported in these species (Balazs and Poley, 1993). Because fresh water turtles are opportunistic scavengers and also take live prey, they are most likely vulnerable to capture with baited hooks set to catch fish (Howey and Dinkelacker, 2013). The present case report discusses the retrieval and management of an entangled fish hook in an Indian flap shelled turtle.